1992
DOI: 10.1007/bf00158576
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in human pathogenic fungi

Abstract: Since the therapy of the mycoses, particularly the systemic mycoses, is relatively long-term in nature, emergence of resistance to antifungal drugs during the treatment of period would be of considerable clinical importance. However, most reports of resistance to antifungal agents among human pathogenic fungi indicate that naturally-occurring resistance is very rare, and that the induction of resistant mutants or variants is much more difficult to achieve in vitro and in vivo than with bacteria. As a matter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 151 publications
(97 reference statements)
1
25
0
1
Order By: Relevance
“…However, we had one strain of C. albicans and other of C. lusitaniae that were resistant and intermediate, respectively, to 5-FC. Isolates of C. albicans primarily resistant to 5-FC have been identified in different clinical materials by several authors, varying in frequency between 0% and 38% (Iwata 1992, Barchiesi et al 2000. The relationship between resistance to 5-FC in C. albicans and serological type was investigated by Drouhet et al (1975), who reported that the percentage of 5FC-resistant strains isolated from patients in Africa was higher than that recovered from patients in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…However, we had one strain of C. albicans and other of C. lusitaniae that were resistant and intermediate, respectively, to 5-FC. Isolates of C. albicans primarily resistant to 5-FC have been identified in different clinical materials by several authors, varying in frequency between 0% and 38% (Iwata 1992, Barchiesi et al 2000. The relationship between resistance to 5-FC in C. albicans and serological type was investigated by Drouhet et al (1975), who reported that the percentage of 5FC-resistant strains isolated from patients in Africa was higher than that recovered from patients in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Primary resistance among C. albicans has been reported to range from 6.5% in Europe to 33% in the United States, with an overall prevalence of 7 to 9% (3,31). C. albicans serotype B, found mainly in Africans and among human immunodeficiency virus (HIV)-infected patients with thrush (18,37), is reported to be significantly more resistant (49%) than serotype A strains (11%) (5). These data were derived by nonstandardized testing methods that have been shown to vary by as much as 10,000-fold when used to determine 5FC MICs for Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…Since 1990, Candida species have continued to be an important cause of nosocomial BSI in the United States, and the proportion (40%-50%) of these infections due to species of Candida other than C. albicans may be increasing ( 12 , 19 , 20 , 31 , 32 ) . Among the species of Candida other than C. albicans, C. glabrata (prone to be resistant to fluconazole) and C. krusei (intrinsically resistant to fluconazole) are of clinical importance 31 , 33 .…”
Section: Discussionmentioning
confidence: 99%